Dual Hesitant N-Soft Sets - Fatia Fatimah (LPPM Institut Teknologi Sepuluh Nopember, 2022)
In this article, we introduce a new hybrid model called Dual Hesitant N-Soft Sets (DHNSS). This new model is clarified and reformulated as a combination of dual and hesitancy with N-soft sets. We investigate the basic operations of DHNSS. Our novel model is illustrated with real life examples. Moreover, we propose the decision making algorithm to see the application of this model.